STUDI MODEL EUCS (END USER COMPUTING SATISFACTION) DAN TAM (TECHNOLOGY ACCEPTANCE MODEL ) TERHADAP PENERIMAAN PENGGUNAAN DAN KEPUASAN PEMAKAI SISTEM INFORMASI BERBASIS KOMPUTER - Wahyu Meiranto; Pratama Agustyan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
Several models have been constructed to analyze and understand the factors that influence theacceptance of the use of computer technology such as Theory of Reasoned Action (TRA), Theoryof Planned Behavior (TPB) and Technology Acceptance Model (TAM). Another model developedby Doll and Torkzadeh (1988) is a model of End User Computing Satisfaction (EUCS). Thisresearch is the study on the TAM and EUCS model of the acceptance and user satisfaction ofcomputer based information system (CBIS). Purpose of this study is trying to use and test the twomodels of acceptance technology, the TAM and EUCS models by examining their influence on theuse and utilization of systems that will ultimately affect the level of user satisfaction (usersatisfaction) as an indicator of the success of a system. Samples used in this study were obtainedfrom the sampling technique based on the criteria (purposive sampling)of a trading company inSemarang, Central Java on the sub-sector (according to the incorporated trading companydirectory-BPS). Test of the hypothesis is formulated using regression models. Three of the sevenstated hypothesis is rejected, while based on the results of the indirect analysis it can be concludedthat the variable utility (usefulness), ease of use, accuracy and timelines in the use of a system alsoaffects the user’s satisfaction.Key Words: Technology Acceptance Model, End User Computing Satisfaction, Computer BasedInformation System, User’s Satisfaction.